Radix Puerarin Extract (Puerarin) Could Improve Meat Quality of Heat-Stressed Beef Cattle Through Changing Muscle Antioxidant Ability and Fiber Characteristics - Li, Yanjiao; Shang, Hanle; Zhao, Xianghui; Qu, Mingren; Peng, Tao; Guo, Beibei; Hu, Yiqing; Song, Xiaozhen (Frontiers in Veterinary Science, 2021)
The experiment was conducted to investigate the effects of dietary supplementing Puerarin on meat quality, muscle antioxidant ability, and muscle fiber characteristics of beef cattle under a hot environment in summer. Thirty-two Jinjiang bulls (291.65 ± 8.84 kg) in 15 ± 1.5 months old were randomly divided into four groups with dietary Puerarin at 0 (control), 200 (Pue200), 400 (Pue400), and 800 (Pue800) mg/kg in the feed concentrate (n = 8). The feeding trial lasted for 60 days after a 10-day adaptation period (1 July to 8 September), the average values of temperature, relative humidity and temperature, and humidity index were 30.68°C, 68.05%, and 81.81, respectively. The growth performance on day 40 of experiment period were calculated. After 60 days experimental period, four Jinjiang cattle per treatment from the control group, the Pue400 and Pue800 group were slaughtered. Compared with the control group, the Pue400 and Pue800 groups improved the growth performance of beef cattle, the Pue800 group elevated the activities of superoxide dismutase, total antioxidant capacity, and glutathione peroxidase in the M. longissimus thoracis (LT) muscle. In the control group, the cell membrane was incomplete, and most of the mitochondria were elongated and in a fission state, while in the Pue400 and Pue800 groups, the cell membrane was clear and complete, and the mitochondria presented with round and oval shapes. Compared with the control group, the Pue400 and Pue800 groups reduced the shear force of LT muscle, the Pue400 group decreased the muscle fiber diameter and the myosin heavy-chain (MyHC)-IIb gene expression. Furthermore, the Pue400 and Pue800 groups decreased the ratio of AMP/ATP, the Pue800 group reduced the AMP-activated protein kinase α2 mRNA expression, the Pue400 group improved the nuclear respiratory factors 1 mRNA expression. These results indicated that dietary supplemented with Puerarin might be beneficial to the meat quality of heat-stressed beef cattle by improving muscle antioxidant ability and reducing the MyHC-IIb muscle fiber composition. Based on the results of this study, we recommended 400 mg/kg Puerarin in the feed concentrate of beef cattle (~300 kg) for mitigation of heat stress.